Identification of uncultured bacteria from abscesses of exotic pet animals using broad-range nested 16S rRNA polymerase chain reaction and Sanger sequencing - T. Duangurai; J. Siengsanan-Lamont; C. Bumrungpun; G. Kaewmongkol; L. Areevijittrakul; T. Sirinarumitr; S. G. Fenwick; S. Kaewmongkol (Veterinary World, 2019)
Background: The Sanger sequencing technique has been questioned and challenged by advanced high-throughput sequencing approaches. Sanger sequencing seems to be an obsolete technology. However, there are still research problems that could be answered using the Sanger sequencing technology. Fastidious obligate anaerobic bacteria are mostly associated with abscesses in animals. These bacteria are difficult to isolate from abscesses and are frequently excluded due to the bias of conventional bacterial culturing.